Hyperleukocytosis in a neonate: A diagnostic dilemma - Sushanth; Avabratha K; Tauro Kiran; Shwethadri G (Indian Journal of Medical and Paediatric Oncology)
A preterm baby presented with lethargy and tachypnea. Blood counts revealed hyperleukocytosis. Peripheral smear and bone marrow examination were not suggestive of leukemia. The baby was treated for sepsis. The baby recovered and WBC counts gradually reduced. Hyperleukocytosis was presumed to be a part of leukemoid reaction secondary to sepsis. The diagnostic possibilities with a review of literature are also presented.